Grounding Eco-Spiritualities: Insights Drawing on Research in Switzerland - Irene Becci (AЯGOS)
The articulation of ecology and spirituality has long-time either be ignored or taken for granted. Rarely has it been approached by a constructivist or processual perspective. This text draws on research on public environmentalism in Switzerland since 2015 when an increasing number of appeals to consider ecological issues with spiritual references appeared. While this observation could not be explained simply by the hypothesis of “greening of religions”, the research asked what the social profiles were of the carriers of this articulation? This text presents how the research has explored life courses of environmentalists to reconstruct the way they have articulated their spiritual or moral ideas with ecology or vice versa. It thereby identifies two main groups who have very different positions in the public realm. The aim of this text is to understand how the two fields of religion—in the broadest sense of the word—and ecology, which were previously quite distinct and relatively impervious to each other, have recently been reshaped in relation to each other, particularly around the notion of eco-spirituality. This text adopts a socio-anthropological perspective to describe eco-spirituality not only as an intellectual category invented in theological and philosophical spheres but as entailing a variety of practices, worldviews, and meaning-making processes interweaving ecology and spirituality.